Unveiling Thrombocytopenia Trends In Pediatric Epilepsy: The Valproate Connection - Nayab, Kiran; Ain, Qurrat ul; Tariq, Ayesha; Liaqat, Israr; Javed, Samra; Mumtaz, Nadia (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the frequency and association of thrombocytopenia in patients on valproate therapy in the Pediatrics department of Pakistan Atomic Energy Hospital, Islamabad. Methods: A descriptive cross-sectional study, conducted in the department of Paediatrics, PAEC General Hospital, Islamabad from 06-June-2022 to 05-December-2022. A total of 125 diagnosed cases of epilepsy and valproic acid therapy were included. After written informed consent from parents/guardians, demographic details were noted, and patients underwent testing for platelet count and thrombocytopenia was labelled as a platelet count of <150000/µL. Results: The mean age of patients included in this study was 8.13±2.80 years. The mean duration of epilepsy was 3.44±1.56 years. Thrombocytopenia was observed in 31 (24.80%) patients on valproic acid therapy and a strong association between higher dosage of valproic acid and thrombocytopenia was observed (p <0.001). Conclusion: An increased risk of thrombocytopenia is observed when valproic acid is used as a monotherapy or a part of polytherapy. Mostly this thrombocytopenia is not life-threatening but the importance of serial monitoring of platelet count during prolonged valproic acid use cannot be ignored due to the associated risk of bleeding, as children on higher doses of valproate are at greater risk of thrombocytopenia. Keywords: Epilepsy, Valproic Acid, Thrombocytopenia.